2018
DOI: 10.1016/j.combustflame.2017.11.027
|View full text |Cite
|
Sign up to set email alerts
|

Gasoline direct injection engine soot oxidation: Fundamentals and determination of kinetic parameters

Abstract: Current emissions legislation for road transport vehicles, including modern gasoline vehicle fleet limits the mass and the number of Particulate Matter (PM) emitted per kilometre. The introduction of a gasoline particulate filter (GPF) is expected to be necessary, as was the case for diesel vehicles, the traditionally recognised source of PM in transportation. Therefore, for the design of efficient GPFs and the regeneration strategies, soot oxidation characteristics in gasoline must be understood. Extensive re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…As required for diesel engines, it is possible to introduce a particulate filter to reduce emissions of soot: the so-called gasoline particulate filter (GPF) [4][5][6]. However, due to the different operating conditions of a diesel engine and a GDI engine [3], it is not possible to simply transfer the technologies optimized and developed in the last twenty years for diesel particulate filters (DPF), but it is necessary to investigate in detail the mechanisms of soot accumulation and oxidation under typical GDI operating conditions [7]. Exactly as it happens for DPFs, the accumulation phase must necessarily be followed by a regeneration phase, in order to oxidize the accumulated soot and prevent an increased pressure drop [8].…”
Section: Introductionmentioning
confidence: 99%
“…As required for diesel engines, it is possible to introduce a particulate filter to reduce emissions of soot: the so-called gasoline particulate filter (GPF) [4][5][6]. However, due to the different operating conditions of a diesel engine and a GDI engine [3], it is not possible to simply transfer the technologies optimized and developed in the last twenty years for diesel particulate filters (DPF), but it is necessary to investigate in detail the mechanisms of soot accumulation and oxidation under typical GDI operating conditions [7]. Exactly as it happens for DPFs, the accumulation phase must necessarily be followed by a regeneration phase, in order to oxidize the accumulated soot and prevent an increased pressure drop [8].…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned trend shows how the particulate produced is much lower than the particle emissions generated by the pool fire (for most advanced SOIs) when the time available for the AF mixture is reduced (most delayed SOIs). In the advanced SOIs, particle formation can persist until the end of the combustion cycle where the rate of heat release can decrease significantly, causing a considerable decrease in the subsequent oxidation phase [69][70][71].…”
Section: Pn Emission Analysismentioning
confidence: 99%
“…The potential for short-term buildup of PM on the GPF and/or the PM's interaction with catalytic active sites, in cases where the emission control catalyst and particulate filter are combined, have created an increased interest in the oxidative reactivity of PM, which would also be relevant when consumer driving behavior requires active regeneration. An understanding of the oxidative reactivity is critical to developing both system models of the powertrain-GPF interactions and operational controls for managing PM accumulation in the GPF [30].…”
Section: Introductionmentioning
confidence: 99%
“…TGA, within a given study, can highlight the effects that a set of conditions has on the activation energy of PM samples; however, variances between experimental procedures used in different reported studies can make direct quantitative comparisons less accurate. The impact of different TGA experimental procedures, such as sample mass, temperature window integration, and ramp rate, has been noted in the literature, and activation energy calculations for PM samples from the same study vary widely, ranging from 67 to 256 kJ/mol [12,[30][31][32]. Wang et al, in a non-isothermal kinetic study, showed that ramp rate and initial PM mass used in the study impacted the calculated activation energy for the same PM [31].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation